Story Map: un nuovo modo di raccontare storie con le mappe - Italia, Esri (GEOmedia, 2014)
The article concern the latest web applications developed by ESRI calls Story Map. These represent a new way of telling stories and are simple to implement, intuitive, open source and have a varied series of application among which the most important are Map Tour, Storytelling text and legend, , Short list and Swipe.